Implementation of A-TH3 Transmitter Sensor for Temperature and Humidity Monitoring System in Furniture Warehouse - Yuvina; Mardiana; Zumhari (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The furniture industry is a potential sector to be developed in Indonesia because it is supported by the availability of abundant natural resources in the country. This furniture market opportunity will continue to grow in the future but must be supported by production factors, namely the provision of quality raw materials, capital and skilled labor. However, this industry is not free from problems such as the quality of raw materials. Wood raw materials in Indonesia are abundant but there is no special treatment to maintain its quality, so the quality of production is hampered. Good wood raw materials are raw materials that avoid damage and weathering. To maintain this quality, the ideal requirement for room temperature for storage is 18oC and room humidity 65%. Changes in temperature and humidity in the storage warehouse always follow changes in temperature and humidity around it. For this reason, further studies are needed on the temperature and humidity monitoring system in the storage warehouse and if there are significant changes, a dehumidifier device is used to keep the temperature and humidity in a room stable.